Persepsi Masyarakat Terkait Implementasi Penggunaan Dana Desa di Desa Mongolato, Kecamatan Telaga, Kabupaten Gorontalo - Hanasi, Raihan A.; Bumulo, Sahrain; Mobilingo, Rapli (Program Studi Sosiologi, Fakultas Ilmu Sosial Universitas Negeri Gorontalo, 2024)
The allocation of Village Funds to each village is a tangible manifestation of the central government's concern for rural development agendas. The primary objective of providing these funds is to enhance the well-being of the community at the village level through the implementation of various development programs tailored to local needs. However, the disbursement of village funds often sparks controversy at the local level, ranging from a lack of transparency to instances of corruption. This research aims to analyze the community's perception regarding the implementation of village fund utilization for sustainable village development. The research methodology employed is qualitative with a descriptive approach. The findings indicate that the implementation of village funds in Mongolato Village has garnered positive responses from the community. The community actively participates in monitoring the use of village funds for development, and the local government allows them to provide feedback, input, and criticism in the development planning process. The Mongolato Village government demonstrates a strong commitment to development to improve the well-being of the community, particularly farmers. In addition to road infrastructure, the village government has also executed various other development programs that have yielded positive impacts.